Adsorption, Aggregation, and Diffusion Behavior of Amyloid β on the Lipid Membrane - Iida-Adachi, Akane; Nabika, Hideki (E-journal of surface science and nanotechnology, 2023)
Understanding the behavior of individual amyloid β (Aβ) monomers, oligomers, and aggregates is important to elucidate the cause of Alzheimer's disease, which has many unsolved mechanistic aspects. In this study, we focused on the behavior of characteristic individual Aβ monomers, oligomers, and fibrils, which were observed using total internal reflection fluorescence microscopy (TIRFM). Specifically, TIRFM enabled observing how each Aβ species adsorbs, aggregates, and diffuses on a lipid membrane. This study, thus, offers a more precise understanding of the dynamic behavior of Aβ on lipid membranes by matching the number of molecules contained in each association with individual Aβ behavior. By tracking the time-course of fluorescence intensities derived from Aβ, the fluorescence intensity of a single Aβ molecule was identified. The diffusivity of Aβ on a lipid membrane revealed that Aβ monomers and oligomers do not always diffuse at a constant rate, but rather change from mobile to immobile and from immobile to mobile states, depending on the number of associations. The adsorption and desorption of Aβ were also observed. Simultaneous observation of fluorescence intensity and diffusivity of each oligomer revealed disassembly from a hexamer to two trimers, followed by desorption of one trimer while the other trimer remains on the membrane. Although the Aβ aggregate was partially adsorbed on the membrane, the non-adsorbed portion was free to move. These results provide new insights and an updated method to gain a better understanding of the aggregation process of Aβ and its contribution to Alzheimer's disease.